Rapid Cycle Deliberate Practice: Application to Neonatal Resuscitation - Karen Patricia; Jennifer Arnold; Daniel Lemke (Association of American Medical Colleges, 2017)
Introduction This curriculum includes two simulation cases for neonatal resuscitation training using the rapid cycle deliberate practice (RCDP) technique. RCDP is a simulation-based curriculum that presents participants with rounds of increasing difficulty in rapid repetition, interspersing brief, direct feedback within the simulation. In contrast, traditional debriefing focuses on learning after the scenario is complete. Traditional debriefing usually utilizes advocacy-inquiry debriefing but allows less opportunity for practice. Methods Each case provides a neonatal resuscitation scenario (respiratory failure secondary to perinatal compromise and cardiac arrest secondary to placental abruption) for a term newborn in the delivery room. The curriculum utilizes high-fidelity neonatal mannequins with learner teams of three to six multidisciplinary teammates who participate in scenarios of increasing difficulty to revive a neonate. Learners can include a spectrum from beginning to advanced neonatal resuscitation providers. Learners are expected to perform the appropriate steps per the neonatal resuscitation program algorithm in addition to exhibiting effective crisis resource management skills. Results Immediate assessment of learner performance and feedback within the RCDP model is more directive, which allows for rapid resumption of practice. The instructor may also choose to pause and back up or to pause and restart, depending on the correction needed. Discussion Neonatal resuscitation program teaching utilizes a neonatal resuscitation performance evaluation, which may be used to guide opportunities for feedback within RCDP.